THE USE OF AN INTERACTIVE EDUCATIONAL PLATFORM IN ORGANIZING THE TEACHING OF” INFORMATICS AND INFORMATION TECHNOLOGY “SCIENCE AND PROFESSIONAL SCIENCES THROUGH” QUEST " TECHNOLOGY (American Journal of Interdisciplinary Research and Development, 2023)
This article presents recommendations for using the capabilities of the interactive educational platform "Joyteka" used in the organization of teaching "Informatics and information technologies" and professional subjects through "Quest" technology. In the course of the modern lesson, the student is expected to acquire the skills of working independently and as a team. It has been shown that relatively new educational technology has a wide and effective scope of application in this regard. The results of the experimental test are given.